Medium/heavy duty truck engines, fuel & computerized management systems - Bennett, Sean (Delmar, Cengage Learning, 2013)
The most comprehensive guide to highway diesel engines and their management systems available today, MEDIUM/HEAVY DUTY TRUCK ENGINES, FUEL & COMPUTERIZED MANAGEMENT SYSTEMS, Fourth Edition, is a user-friendly resource ideal for aspiring, entry-level, and experienced technicians alike. Coverage includes the full range of diesel engines, from light duty to heavy duty, as well as the most current diesel engine management electronics used in the industry. The extensively updated fourth edition features nine new chapters to reflect industry trends and technology, including a decreased focus on outdated hydromechanical fuel systems, additional material on diesel electric/hydraulic hybrid technologies, and information on the principles and practices underlying current and proposed ASE and NATEF tasks. With an emphasis on today's computer technology that sets it apart from any other book on the market, this practical, wide-ranging guide helps prepare you for career success in the dynamic field of diesel engine service